Antenatal psychosocial assessment and depression screening in a private hospital. (30th October 2015) - Kohlhoff, Jane; Hickinbotham, Rachael; Knox, Catherine; Roach, Vijay; Barnett Am, Bryanne
Abstract : Background: It has been recommended that psychosocial assessment (including depression screening) be integrated into routine antenatal care across Australia, but implementation in the private sector has lagged. Aims: This study aimed to report preliminary outcomes associated with an antenatal psychosocial assessment and depression screening program implemented at an Australian private obstetric hospital setting and to report characteristics and correlates of elevated depression symptoms in this sample. Materials and Methods: A total of 993 pregnant women (mean ± SD gestational age 27.9 ± 6.7 weeks) participated in a structured psychosocial assessment interview and completed the Edinburgh Postnatal Depression Scale (EPDS). Results: Six per cent of participants scored ≥13 on the EPDS. Psychosocial correlates of antenatal depressive symptoms included low income, history of pregnancy termination, poor practical support, lack of confidence and history of depression. Almost 1 in 10 of the total sample was referred for further assessment and clinical support. Conclusions: The prevalence of clinically significant antenatal depressive symptoms in this sample highlights the importance of antenatal depression screening for all women, including those who choose to access private obstetric care.